Crosslinguistic Influence in Learning Thai as a Third Language: Perspectives of Indonesian Ph.D. Candidates in Thailand - Didit Haryadi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This study examines the perspectives of Indonesian Ph.D. candidates in Thailand on the similarities and differences among Indonesian, English, and Thai languages, as well as the influence of Indonesian and English on learning Thai as a third language. A qualitative method with a phenomenological approach was used to analyze data gathered from four Indonesian Ph.D. candidates from different majors. The study found that there are several linguistic features shared between Indonesian, English, and Thai languages, including pronunciation, English loanwords, basic sentence structure, word order, and honorific terms and formality. These linguistic similarities facilitated the participants' learning of the Thai language as a third language. Moreover, the findings revealed that the participants' educational background played a significant role in the positive language transfer from their first and second languages to Thai. The study recommends that language educators and policymakers should acknowledge the importance of educational background in facilitating positive language transfer in third language acquisition. Furthermore, language programs should be designed to encourage multilingualism and code-switching in the classroom to promote students' linguistic awareness and proficiency. Additionally, language learners could benefit from opportunities to interact with native speakers and practice their language skills in real-world settings.